The impact of proptech on real estate industry growth. Issue 6 (June 2020) - Siniak, Nikolai; Kauko, Tom; Shavrov, Sergey; Marina, Ninoslav
Abstract: The real estate industry is currently undergoing a digital transformation that not only changes its nature in terms of the markets and work environments, but is also influencing its growth. What are the main trends and concerns related to this transformation? To what extent is the real estate industry already prepared for this? This paper reviews the situation in terms of the emergence of a phenomenon known as PropTech. PropTech is characterized by the massive implementation of emerging technology such as home matching tools, drones, virtual reality, building information modelling (BIM), data analytics tools, artificial intelligence (AI), Internet of Things (IoT) and blockchain, smart contracts, crowdfunding in the real estate sector, fintechs related to real estate, smart cities, regions, smart homes and shared economy. This survey of changes in the real estate industry due to PropTech covers four areas: (1) PropTech applications in the real estate industry; (2) implications of PropTech for real estate market transparency; (3) how PropTech could give a region or a company a competitive advantage; and (4) concerns on the wider implications of these changes on a labour market and education. In a plausible scenario, changing the real estate technologies could change system dynamics and improve real estate market transparency. Moreover, it can be asserted that, in a broader sense, PropTech is beneficial for territorial competition and territorial growth strategies. And lastly, under different institutional arrangements, PropTech can affect the changing structure of the real estate market, the demand for hi-tech, new skills as well as emerging policy challenges for the real estate industry.